Audit Committee Characteristics and Timeliness of Financial Reports in Nigeria - Edosa Joshua Aronmwan; Monye-Emina Henry Emife (Journal of Danubian Studies and Research, 2022)
This study examines the nexus between audit committee characteristics and timeliness of financial reports in Nigeria. The study employed correlation research design using the annual report of thirteen (13) listed deposit money banks in Nigeria for the period 2016 - 2020. Timeliness of financial reports was measured as a categorical variable that assumed the value of one (1) for banks that released their annual report within the 90 days stipulated by the regulatory agency and zero (0) for those that fail to meet this requirement. Audit committee independence was measured using proportion of independent non-executive directors on audit committee; audit committee meeting was measured using number of meetings held in a year; audit committee financial expertise was measured using the proportion of members who have accounting or financial management knowledge while audit committee gender diversity was measured using the number of women on the board. The data for the study were analyzed using descriptive statistics, Pearson correlation and binary logit regression technique. The results show that audit committee meeting has a statistically significant relationship with timeliness of financial reports and the relationship was negative. Other audit committee attributes did not have any significant relationship with timeliness of financial reporting. Flowing from the findings, the study recommends that money deposit banks should ensure that meetings held by the audit committee are managed so that deliberations do not lead to untimely release of financial reports.